The Struggle for Narrative Space: The Decoloniality of Palestine in Bāsim Khandaqjī’s Qinā‘un bi Launi As-Samā`i - Alfi Nur Khoirunnisa; Monica Widiany Kusteja (POETIKA, 2026)
Bāsim Khandaqjī's novel Qinā'un bi Launi As-Samā'i (QBLS) attempts to create a narrative space for Palestinian history through a plot rich in historical and archaeological details. Using Walter Mignolo's theory of decoloniality, this study examines how Israel colonizes knowledge through its narratives. It also analyzes how QBLS performs decoloniality through epistemic disobedience against Israeli colonialism. A qualitative descriptive methodology was employed to investigate the colonial mechanisms embedded in the Israeli occupation. The findings reveal that Israeli colonialism in the realm of knowledge operates through the distortion of Palestinian historical narratives and collective experiences, including the denial of the crimes of An-Nakbah and the Hebraization and demonization of Palestinian resistance. This narrative is sustained through continuous retelling based entirely on colonial perspectives while excluding Palestinian lived experiences. These mechanisms are embedded in both explicit and implicit narrative structures, including the symbolic erasure of Arab cultural heritage, as exemplified by the narrative surrounding Mary Magdalene. Conversely, the novel articulates decolonial resistance by foregrounding local knowledge derived from Palestinian lived experiences and presenting it through a coherent, evidence-based narrative. This epistemic disobedience challenges assumptions of Western epistemological superiority and opens space for marginalized perspectives. The study underscores the role of literature as a tool of resistance and affirms Palestinian identity in the face of institutionalized oppression.